The pathophysiology of non-steroidal anti-inflammatory drug (NSAID)-induced mucosal injuries in stomach and small intestine - Matsui, Hirofumi (the Society for Free Radical Research Japan, 2011)
Non-steroidal anti-inflammatory drugs are the most commonly prescribed drugs for arthritis, inflammation, and cardiovascular protection. However, they cause gastrointestinal complications. The pathophysiology of these complications has mostly been ascribed to non-steroidal anti-inflammatory drugs’ action on the cyclooxygenase inhibition and the subsequent prostaglandin deficiency. However, recent clinical demonstrated the prevalence of non-steroidal anti-inflammatory drugs-induced small intestinal mucosal injury is more often than previously expected. In this review, we discuss the defense mechanisms of stomach, and the pathophysiology of non-steroidal anti-inflammatory drugs-induced injury of stomach and small intestine, especially focused on non-steroidal anti-inflammatory drugs’ action on mitochondria.